THE ROLE OF SECURITY PERSONNEL IN EFFORTS TO PREVENT ACTS OF VIOLENCE IN CLASS IIB SUKADANA CORRECTIONAL FACILITY - Azka, Aqori Satria; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
This study examines the role of security officers in preventing violence at the Sukadana Class IIB State Detention Center. The overcrowding of inmates at the Sukadana Detention Center poses a higher security risk, including violence among inmates. The study aims to identify the role of security officers in preventing violence and to reveal the challenges they face in carrying out their duties. Using a qualitative approach, data were collected through observations, interviews with correctional officers, and relevant documentation. Role theory by Biddle and Thomas was used as a framework to analyze expectations, norms, performance, and evaluations of the officers' role in maintaining security. The findings show that officers play a central role in preventing violence, although they face several challenges, such as the limited number of personnel, which is insufficient compared to the number of inmates. Preventive measures include regular patrols, monitoring inmate interactions, and supervising items brought by visitors. In conclusion, security effectiveness needs to be improved by increasing personnel and enhancing the facilities at the detention center. Keywords: Prevention of Violence; Security and Order; Overcapacity